Kapasitas Petani Jagung di Kabupaten Serang: Analisis Multidimensi - Asih Mulyaningsih; Ari Tresna Sumantri; Sri Mulyati (JURNAL AGRIBISNIS TERPADU, 2026)
Maize farming in smallholder regions increasingly requires farmers to combine agronomic competence with managerial, economic, social, adaptive, and information-based capacities. This study analyzed the multidimensional capacity profile of maize farmers in Serang Regency, Banten Province, Indonesia. A descriptive quantitative survey was conducted with 82 maize farmers in Pemarasan, Jawilan, and Kopo sub-districts. Farmer capacity was assessed across six dimensions and classified into high, medium, and low categories. A diagnostic capacity index was calculated by assigning scores of 3, 2, and 1 to the categories and normalizing the weighted mean to a 0–100 scale. The results indicate an asymmetric capacity profile. Technical capacity was the strongest dimension, with 39.02% of farmers classified as high and an index of 68.70. In contrast, managerial, economic, social, adaptive, and information-extension capacities were dominated by the medium category. Social capacity recorded the lowest index (64.23), while managerial capacity showed the highest strengthening load (75.61%). These findings suggest that the main constraint is not basic cultivation knowledge but the limited ability to transform technical competence into resilient, profitable, and collectively supported farming. The article proposes an integrated capacity-strengthening agenda focused on farmer-group revitalization, farm-business planning, usable finance, climate-responsive extension, and hybrid information systems.